Comparative Study to Video Tutorial and Peer Tutor on Student’s Learning Outcomes on 2 Dimensional Animation Techniques - Kartika Mukti, Maria Linda; Basori, Basori; Budiyanto, Cucuk W (Universitas Sebelas Maret, 2019)
This research purpose is (1) to know the difference of learning outcomes from the utilization of video tutorials and peer tutors (2) to find out the effectiveness between the utilization of video tutorials and peer tutors towards students’s learning outcomes on 2 dimensional Animation Technique subject at second grade.Research method used in this research is quantitative method of quasi experimental with pre-test and post-test type. Data collection techniques in this reasearch with (1) observation (2) t test by using a pre-test and post-test (3) and documentation.The results obtained from this research are (1) there are differences of learning outcomes of students between utilization of video tutorial and peer tutors with the calculated of post-test value of each class using the t test independet amounted to 0,032. (2) the utilization of peer tutors in this research is more effective than the utilization of video tutorials, this calculation outcomes obtained from a test of gain in each class. On video tutorial class gets the calculation outcomes of 0.32, while on peer tutor class gets the calculation outcomes of 0.58.Keywords: video tutorials, peer tutor, 2 dimensional animation, learning outcomes